Politik Pemberantasan Korupsi di Indonesia - Suherry Suherry (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
This article discusses the politics of eradicating corruption in Indonesia. The most difficult problem in the running of the government process is due to the massive corruption, collusion and nepotism practices that have impacted widely on society. Corruption in the legal world is classified as an extraordinary crime because it not only harms the State's finances, but also practices violate the social and economic rights of society widely so that its eradication measures must also be done in an extraordinary way. That is what is disclosed in the consideration of the Law on the Eradication of Corruption. Through a juridical-empirical approach of this article, the question of corruption in Indonesia is well answered. Artikel ini membahas tentan politik pemberantasan korupsi di Indonesia. Masalah tersulit dalam berjalannya proses pemerintahan dikarenakan massifnya praktik korupsi, kolusi dan nepotisme yang meraja lela yang berdampak secara luas bagi masyarakat. Korupsi dalam dunia hukum sudah tergolong sebagai extra ordinary crime (kejahatan luar biasa) karena tidak hanya merugikan keuangan Negara, tetapi juga praktik tersebut melanggar hak-hak sosial dan ekonomi masyarakat secara luas sehingga tindakan pemberantasannya harus juga dilakukan dengan cara yang luar biasa pula. Begitulah yang diungkapkan dalam konsideran Undang-Undang Tentang Pemberantasan Tindak Pidana Korupsi. Melalui pendekatan yuridis-empiris, pertanyaan terkait pemberatasan korupsi di Indonesia terjawab dengan baik.